Comparing the Feasibility and Economic Performance of Rice Farming in Pandan Enim Village Using Local Microorganisms (MOL) - Putri Ayu Ogari; Endang Lastinawati; Erikawati; Henny Rosmawati; Ema Pusvita; Windi Lestari; Chuzaimah; Trisna Wahyu Swasdiningrum Putri (Journal of Global Sustainable Agriculture, 2025)
The use of Local Microorganisms (LOM) in rice farming is an effort to utilize local resources and reduce cultivation practices that use chemical inputs. This study aims to compare the income and feasibility of lowland rice farming between farmers who use and those who do not use LOM in Pandan Enim Village, Tanjung Agung District, Muara Enim Regency. The research method used is a case study with a stratified disproportionate random sampling technique, each involving 15 LOM users and 15 non-LOM users. Data are described mathematically using the farm income formula and the ratio of revenue to production costs. The results indicate that increased rice production leads to higher incomes for LOM users compared to non-LOM users. The R/C value in the LOM user group is also greater than 1 and higher than the non-LOM user group, so rice farming with the application of LOM is declared more feasible to cultivate. Thus, the use of LOM is proven to provide better economic benefits and is worthy of being recommended as an efficient and sustainable rice crop management technology at the farmer level.